Cardiovascular effects of long‐duration space flight - Iqbal Hussain; Rehmat Ullah; Bharti F. N. U. Simran; Parvinder Kaur; Mahendra Kumar; Rohan Raj; Maria Faraz; Amin Mehmoodi; Jahanzeb Malik (Health Science Reports, 2024)
Abstract Introduction Early studies exploring the physiological effects of space travel have indicated the body's capacity for reversible adaptation. However, the impact of long‐duration spaceflight, exceeding 6 months, presents more intricate challenges. Effects on the Cardiovascular (CV) System Extended exposure to microgravity and radiation profoundly affects the CV system. Notable phenomena include fluid shifts toward the head and modified arterial pressure. These changes disrupt blood pressure regulation and elevate cardiac output. Additionally, the loss of venous compression leads to a reduction in central venous pressure. Fluid and Plasma Volume Changes The displacement of fluid from the vascular system to the interstitium, driven by baroreceptor stimulation, results in a 10%–15% decline in plasma volume. Cardiac Muscle and Hematocrit Variations Intriguingly, despite potential increases in cardiac workload, cardiac muscle atrophy and perplexing variations in hematocrit levels have been observed. The mechanism underlying atrophy appears to involve a shift in protein synthesis from the endoplasmic reticulum to the mitochondria via mortalin‐mediated mechanisms. Arrhythmias and QT Interval Prolongation Instances of arrhythmias have been recurrently documented, although generally nonlethal, in both Russian and American space missions. Long‐duration spaceflight has been associated with the prolongation of the QT interval, particularly in extended missions. Radiation Effects Exposure of the heart to the proton and heavy ion radiation pervasive in deep space contributes to coronary artery degeneration, augmented aortic stiffness, and carotid intima thickening through collagen‐mediated processes. Moreover, it accelerates the onset of atherosclerosis and triggers proinflammatory responses. Reentry and Postflight Challenges Upon reentry, astronauts frequently experience orthostatic intolerance and altered sympathetic responses, which bear potential hazards in scenarios requiring rapid mobilization or evacuation. Conclusion Consequently, careful monitoring of these cardiac risks is imperative for forthcoming missions. While early studies illuminate the adaptability of the body to space travel's challenges, the intricacies of long‐duration missions and their effects on the CV system necessitate continued investigation and vigilance to ensure astronaut health and mission success.